(untitled) (Entrepreneurship Journal for Finance and Business, 2025)
This research aims to emphasize and focus on sustainable environmental strategies in urban planning of cities and to provide appropriate solutions to most of the problems resulting from incorrect land use and not distributing it in consistent and studied proportions according to a strategic vision that contributes to improving the environmental aspect of cities in the long term. The results showed that the total per capita share in the city of Ramadi amounted to (664.1) square meters in terms of area. The most important outcomes of the SPSS program were that the male participation rate was (78.7), and the female rate was (21.3). Regarding the axis of residential use and urban condition, a percentage of (3.67) appeared.). The results of the correlation analysis also showed that there is a positive, significant correlation between all dimensions of urban planning and proactive environmental sustainability, and the regression results showed that there is a positive, significant effect between proactive environmental sustainability on the dimensions of urban planning, which means accepting the basic research hypothesis, which is the presence of a positive effect of proactive environmental sustainability on urban planning.